Sic nudus et armatus in Christo solitudinem ingressus est... (The Motif of Desert in St. Jerome's Legends about the Hermits) - ŠUBRT, JIŘÍ (Listy filologické / Folia philologica, 2000)
The desert in hagiographic narratives thus represents an ambivalent space which lies somewhere on the boundary line between the real world and the imaginative one. It has something of the menace of the real desert and at the same time it is a sacred place where God's presence is felt more clearly and Christianization has gone further than in places of human civilisation. This place bears typical signs of transition or border area46 combining contradictory features of the sacred and profane settings. The real world and the miraculous one meet here co-existing freely alongside each other. As it is a space of temporary existence, full of contradictions and discrepancies, it is also a space of searching and finding. Antony follows in animals' footsteps (ferarum tantum vestigia intuens, et eremi tantam vastitatem) in order to find Paul in his paradise; and when he finds him and Paul refuses to let him in he protests with a quotation from the Bible: Quaesivi et inveni: pulso ut aperiatur.47 Malchus in turn, despite his unenviable position as a prisoner of Arab robbers, finds in himself thanks to the desert the monk whom he almost betrayed because of worldly possessions (Delectabat me captivitas mea; agebamque Dei judicio gratias, quod monachum, quem in patria fueram perditurus, in eremo inveneram).48